Long-Term Caloric Restriction Improves Cardiac Function, Remodeling, Adrenergic Responsiveness, and Sympathetic Innervation in a Model of Postischemic Heart Failure. (March 2018) - de Lucia, Claudio; Gambino, Giuseppina; Petraglia, Laura; Elia, Andrea; Komici, Klara; Femminella, Grazia Daniela; D'Amico, Maria Loreta; Formisano, Roberto; Borghetti, Giulia; Liccardo, Daniela; Nolano, Maria; Houser, Steven R.; et al.
Abstract : Background: Caloric restriction (CR) has been described to have cardioprotective effects and improve functional outcomes in animal models and humans. Chronic ischemic heart failure (HF) is associated with reduced cardiac sympathetic innervation, dysfunctional β-adrenergic receptor signaling, and decreased cardiac inotropic reserve. We tested the effects of a long-term CR diet, started late after myocardial infarction on cardiac function, sympathetic innervation, and β-adrenergic receptor responsiveness in a rat model of postischemic HF. Methods and Results: Adult male rats were randomly assigned to myocardial infarction or sham operation and 4 weeks later were further randomized to a 1-year CR or normal diet. One year of CR resulted in a significant reduction in body weight, heart weight, and heart weight/tibia length ratio when compared with normal diet in HF groups. At the end of the study period, echocardiography and histology revealed that HF animals under the CR diet had ameliorated left ventricular remodeling compared with HF rats fed with normal diet. Invasive hemodynamic showed a significant improvement of cardiac inotropic reserve in CR HF rats compared with HF-normal diet animals. Importantly, CR dietary regimen was associated with a significant increase of cardiac sympathetic innervation and with normalized cardiac β-adrenergic receptor levels in HF rats when compared with HF rats on the standard diet. Conclusions: We demonstrate, for the first time, that chronic CR, when started after HF established, can ameliorate cardiac dysfunction and improve inotropic reserve. At the molecular level, we find that chronic CR diet significantly improves sympathetic cardiac innervation and β-adrenergic receptor levels in failing myocardium. Abstract : Supplemental Digital Content is available in the text.